2017
DOI: 10.1039/c7ra10247j
|View full text |Cite
|
Sign up to set email alerts
|

Determination of pentachlorophenol by anodic electrochemiluminescence of Ru(bpy)32+ based on nitrogen-doped graphene quantum dots as co-reactant

Abstract: Sensitive and quantitative analysis of pentachlorophenol (PCP) is especially important in the field of ecology and agriculture. Herein, a highly sensitive and stable Ru(bpy) 3 2+-based anodic electrochemiluminescence (ECL) system utilizing nitrogen-doped graphene quantum dots (NGQDs) as a novel co-reactant was firstly constructed to detect PCP. In this system, Ru(bpy) 3 2+ was used as luminophor, while NGQDs were applied as co-reactant in place of the toxic and volatile tripropylamine. The novel co-reactant no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The conclusion was supported by the finding that conversion of primary amine on NCDs to tertiary amines through an Eschweiler‐Clarke methylation reaction could further increase the ECL enhancement. Furthermore, GQDs, nitrogen‐doped GQDs (NGQDs) and graphene oxide (GO) can also enhance anodic Ru(bpy) 3 2+ ECL by using amine group, carboxyl group, alcohols, phenols and other oxygenated groups as co‐reactant sites …”
Section: Ru(bpy)32+‐nanomaterials Co‐reactant Eclmentioning
confidence: 99%
See 3 more Smart Citations
“…The conclusion was supported by the finding that conversion of primary amine on NCDs to tertiary amines through an Eschweiler‐Clarke methylation reaction could further increase the ECL enhancement. Furthermore, GQDs, nitrogen‐doped GQDs (NGQDs) and graphene oxide (GO) can also enhance anodic Ru(bpy) 3 2+ ECL by using amine group, carboxyl group, alcohols, phenols and other oxygenated groups as co‐reactant sites …”
Section: Ru(bpy)32+‐nanomaterials Co‐reactant Eclmentioning
confidence: 99%
“…With the discoveries, a plenty of ECL bio‐/chemo‐sensors have been developed by taking advantage of good biocompatibility of nanomaterials and the strong and stable ECL emission from Ru(bpy) 3 2+ /nanomaterials systems. For example, a signal‐off pentachlorophenol ECL sensor was fabricated based on the Ru(bpy) 3 2+ /NGQDs ECL system . In the presence of pentachlorophenol, the ECL intensity of Ru(bpy) 3 2+ /NGQDs system was quenched due to the energy transfer between electrooxidation product of pentachlorophenol and Ru(bpy) 3 2+ *.…”
Section: Ru(bpy)32+‐nanomaterials Co‐reactant Eclmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 4A showed that the optimal volume of NH 2 À SiO 2 was 4.0 μL. It was because that more ECL luminophore Ru(bpy) 3 2 + was modified on the GCE surface and produced more excited states of Ru (bpy) 3 2 + * [41]. Excessively adding of Ru(bpy) 3 2 + À UiO66 caused the quenching of ΔECL intensity, since too thick film modified on GCE surface hindered the electron transfer rate.…”
Section: Optimization Of Conditionsmentioning
confidence: 99%